Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1021/om501208x
|View full text |Cite
|
Sign up to set email alerts
|

The Structural Effect of Methyl Substitution on the Binding of Polypyridyl Ru–dppz Complexes to DNA

Abstract: Polypyridyl ruthenium complexes have been intensively studied and possess photophysical properties which are both interesting and useful. They can act as probes for DNA, with a substantial enhancement in emission when bound, and can induce DNA damage upon photoirradiation. Therefore the synthesis and characterization of DNA binding of new complexes is an area of intense research activity. While the knowledge of how the binding of derivatives compares to the parent compound is highly desirable, this information… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
27
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 32 publications
4
27
0
Order By: Relevance
“…The structure of the binding site and DNA is virtually identical in structures 1 – 3 and, therefore, they will be discussed as a single entity from now on. However, the fact that they are so similar shows that there is little difference in binding between bpy and phen‐based Λ complexes (Figure S2 in the Supporting Information) and that methyl‐substitution at the 11th and 12th positions on the dppz does not change how the compounds bind, which is consistent with the crystal structure of Λ‐[Ru(TAP) 2 (dppz‐11,12‐Me)] 2+ bound to d(TCGGCGCCGA) 2 . This observation shows that, as long as no major structural changes are made, Λ‐Ru‐dppz complexes can be treated as a single class of compound when it comes to their binding specificity.…”
Section: Figuresupporting
confidence: 72%
“…The structure of the binding site and DNA is virtually identical in structures 1 – 3 and, therefore, they will be discussed as a single entity from now on. However, the fact that they are so similar shows that there is little difference in binding between bpy and phen‐based Λ complexes (Figure S2 in the Supporting Information) and that methyl‐substitution at the 11th and 12th positions on the dppz does not change how the compounds bind, which is consistent with the crystal structure of Λ‐[Ru(TAP) 2 (dppz‐11,12‐Me)] 2+ bound to d(TCGGCGCCGA) 2 . This observation shows that, as long as no major structural changes are made, Λ‐Ru‐dppz complexes can be treated as a single class of compound when it comes to their binding specificity.…”
Section: Figuresupporting
confidence: 72%
“…[16] Recently we explored the structural effect of substitution on the distal ring of the dppz ligand in [Ru(TAP) 2 (dppz)] 2+ . [17] We found that the addition of an itrile substituent to give [Ru(TAP) 2 (11-CN-dppz)] 2+ (1;F igure 1a)c aused (so far uniquely) the formation of ac omplete intercalation cavity when the lambda complex (L-1)b ound to the d(TCGGCGCCGA) duplex, [18] thus showing that even this small modification of the dppz ligand strengthened the stacking interaction. Based on this finding, we explored the binding of compound 1 with aG -quadruplex-forming sequence,r easoning that aG -quartet has al arger surface area available for p stacking and therefore could accommodate the full footprint of the derivatised dppz group.T his led not only to the first crystal structure showing amononuclear ruthenium polypyridyl complex bound to aD NA G-quadruplex but also shed light on the structure-selective luminescence behaviour of the isostructural analogue [Ru(phen) 2 (11-CN-dppz)] 2+ (2).…”
mentioning
confidence: 85%
“…In contrast to this, the interaction of the Λ enantiomer appears relatively straightforward: Λ-[Ru(phen) 2 (dppz)] 2+ has been shown to intercalate into well-matched DNA and, both it and the isostructural Λ-[Ru(TAP) 2 (dppz)] 2+ , bind selectively to 5′-TA-3′ steps and not 5′-AT-3′ in both the crystal state and solution (15). The effects of introducing methyl (16) and chloro (17) substitutions onto the dppz group have also been examined, and the resulting DNA structures were isomorphous with those reported for the parent compound, while displaying site preferences for asymmetric substitution.…”
Section: Introductionmentioning
confidence: 99%